2016
DOI: 10.6023/cjoc201605007
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Hypervalent Iodine Chemistry

Abstract: In recent years, an explosive growth of reactivities of hypervalent iodine reagents has witnessed and these reagents, featuring facile availability and easy handleness, offer multiple advantages over establised methods as an efficient multipurpose oxidants, whose reactivities are similar to derivatives of mercury, chromium, lead, thallium and other heavy metals, but without the toxicity and environmental problems of these heavy metal agents. Thus, hypervalent iodine reagents have received much more attention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In 2012, Du and Zhao reported a synthesis of racemic spirocyclic bis-oxindoles from N 1 , N 3 -diarylmalonamides through a PIFA­[PhI-(TFA) 2 ]-promoted intramolecular oxidative coupling (Scheme a). , In 2014, Gong and co-workers developed such reactions further, achieving an elegant catalytic asymmetric version with chiral iodoarenes and oxidants (Scheme b) . However, because of the incompatibility of some functional groups with oxidative conditions and the complexity of reactions mediated by iodine reagents, serious limitations and challenges to these synthetic efforts still persisted, including limited substrate scope, moderate reaction efficiency, and poor regioselectivity . Further efforts may also be needed for further improvement of the enantioselectivity of such reactions.…”
mentioning
confidence: 99%
“…In 2012, Du and Zhao reported a synthesis of racemic spirocyclic bis-oxindoles from N 1 , N 3 -diarylmalonamides through a PIFA­[PhI-(TFA) 2 ]-promoted intramolecular oxidative coupling (Scheme a). , In 2014, Gong and co-workers developed such reactions further, achieving an elegant catalytic asymmetric version with chiral iodoarenes and oxidants (Scheme b) . However, because of the incompatibility of some functional groups with oxidative conditions and the complexity of reactions mediated by iodine reagents, serious limitations and challenges to these synthetic efforts still persisted, including limited substrate scope, moderate reaction efficiency, and poor regioselectivity . Further efforts may also be needed for further improvement of the enantioselectivity of such reactions.…”
mentioning
confidence: 99%
“…Hypervalent iodine reagents have attracted considerable attention of synthetic chemists due to their rich reactivities, low toxicity, ready, availability, and recyclability (Varvoglis, 1997;Zhdankin andStang, 2002, 2008;Wirth, 2005;Brown et al, 2013;Singh and Wirth, 2014;Zhdankin, 2014;Duan et al, 2016;Li et al, 2016;Yoshimura and Zhdankin, 2016;Han and Zhang, 2018;Liu et al, 2019). In 2012, we first reported that iodosodilactone, a bicyclic benziodoxole compound, could function as a coupling reagent to promote the efficient syntheses of esters, macrocyclic lactones, amides, and peptides in the presence of PPh 3 at 60 o C (Scheme 1) (Tian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hypervalent iodine reagents, due to their safety, ready availability, environmental friendliness, and regenerability, are preferred organo-oxidants in the organic synthesis . In this study, as part of our ongoing exploration of the reactivity of AIBX (5-trimethylammonio-1,3-dioxo-1,3-dihydro-1λ 5 -benzo­[ d ]­[1,2]­iodoxol-1-ol anion), a water-soluble hypervalent iodine­(V) reagent that was first synthesized in our laboratory, we developed an efficient method for oxidative formation of epoxide groups directly from C sp2 –C sp3 single bonds in a single step using AIBX as an oxidant in the absence of a catalyst (Figure E).…”
Section: Introductionmentioning
confidence: 99%